A meta-analysis of the soft tissue defects classification and justification of the optimal surgical reconstruction method - Sergiy Tertyshnyi; Igor Khomenko; Кostyantyn Gumenyuk; Sergiy Korol; Yevgen Tsema; Dmytro Dubenko; Rostyslav Mikhaylusov; Mykola Grinchuk; Oksana Popova (Bogomolets National Medical University, 2021)
During the military conflict in the East of Ukraine, considerable experience in providing medical assistance to wounded and injured with soft tissue defects has been accumulated. Taking into account the considerable diversity of defects of soft tissues on numerous a number of signs, which involves the application in the process of treatment of fundamentally different algorithms of preoperative training, planning of reconstructive intervention and method of surgical reconstruction there was a need to systematize the accumulated knowledge by developing the integral classification of soft tissue defects.